SINTESIS KITOSAN SUKSINAT DARI KITOSAN DAN SUKSINAT ANHIDRID SERTA KARAKTERISTIKNYA - melati, Arsyi; Iskandar, Dodi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
The purpose of this study was to determine the effect of molecular weight of chitosan towards the solubility of chitosan succinate in water. The chitosan succinate was synthesized by succinilation method. In the synthesis, chitosan with different molecular weight, low molecular weight (LMW), medium molecular weight (MMW), high molecular weight (HMW) were reacted with succinate anhydride (1:10) for 24 hours. The infrared spectra of chitosan succinate, showed by wavenumber shift, indicating that there has been interaction between chitosan and succinate anhydride. Based on results of analysis of the characterization of chitosan succinate (Analysis of nitrogen,analysis of degree of substitution, and solubility test in water), succinate chitosan HMW (High Molecular Weight) has the highest level of solubility. At temperature of 800C, it dissolves until 99.34% of solubility, the succinate chitosan has 2.98% of nitrogent content, and 0.60 of degree of substitution. From this research can be inferred that larger molecular weight of chitosan can lead into a higheer degree of substitution and solubility values in water.